Analisis Pengaruh Komitmen Kerja, Disiplin Kerja, dan Kompetensi terhadap Kinerja Guru pada Sekolah Guang Ming Medan - Albert, Albert; Prasetio, Meriyawaty Amelia; Patera, Agusting Sebastian; Angkasa, Marco; William, Justin Sebastian (Journal of Community Research and Service, 2025)
The purpose of this study was to determine, analyze, and examine the effect of work commitment, work discipline, and competence to teachers performance in Sekolah Guang Ming Medan. The research approach used is quantitative with the type of survey research. The total population in this study is 53 people and a sample of 53 people with census sampling techniques in which all members of the population were research samples. Data collection was carried out using a questionnaire instrument. Data analysis techniques used are validity test, reliability test, descriptive analysis, normality test, heterokedastisities test, multicollinearity test, multiple linear analysis, multiple linear correlation coefficient test, partial hypothesis test or t test, simultaneous hypothesis test or F test, and calculation coefficient of determination. The results of descriptive analysis for work commitment variables and work discipline variables are in the very good category, while the competence and teacher performance variables are in the good category, at Sekolah Guang Ming Medan. Based on partial analysis, work commitment, work discipline, and competence have a positive and significant effect on teacher performance at Sekolah Guang Ming Medan. Simultaneously, work commitment, work discipline, and competence have a positive and significant impact on teacher performance at Sekolah Guang Ming Medan. The contribution of the work commitment, work discipline, and competence variables to improve teacher performance variables is 0.812 or 81.2%, while the remaining 0.188 or 18.8% is influenced by other variables not examined by the authors in this study, such as leadership, work motivation, organization culture and so on.